POLA PERJALANAN DESA WISATA SOOKA KABUPATEN PACITAN - Aryosamodro, Noor Harsya; DWI ATMAJA, NUR RAHMAT ARDI CANDRA (Institut Seni Indoensia Surakarta, 2016)
Life of the community adapt to the environment of the mountains Sewu in Pacitan was an extraordinary experience as a shared learning. Environmental influences and untapped natural potential as aÂ knowledge of the history of the earth is not yet considered the potential. Along with the spirit andincredible work ethic encourage villagers in Pacitan build a tourist village efforts as new destinations in Pacitan. Tourist village into a model development of creative economic development as aÂ basis of economic growth in the region and regionally in East Java. The field research uses an ethnographic approach as an attempt to read the dynamics of society and read the regulation on tourism inPacitan. An ethnographic approach â€œbeingâ€ or ontology of this research project wants a â€œmappingâ€Â or the travel patterns of rural tourism so as to contribute to government policy. Government policiesÂ in the three (3) provinces, namely, East Java, Central Java and Yogyakarta associated with the receiptÂ of the plan penggunungan Sewu region into areas of â€œgeo karstâ€ in the UN world body UNESCO.Â Travel patterns tourist village Sooka as micro area managed by the society has tremendous potentialÂ mobilize community-based economy. Objects managed by communities and re-enjoyed by the public isÂ an important pillar of the new economy as an alternative income increase Sooka Village community.The pattern has been found Sooka Tourism Village Travel, Travel Pattern 1, Pattern 2 and PatternÂ Journey Journey 3. The third pattern that has various advantages and disadvantages of each.Keywords: travel pattern, village tourism Sooka, community-based management